Signaling of ERBB Receptor Tyrosine Kinases Promotes Neuroblastoma Growth in vitro and in vivo - Richards, Kristen N. (2010)
BACKGROUND: ERBB receptor tyrosine kinases can mediate proliferation, migration, adhesion, differentiation, and survival in many types of cells and play critical roles in many malignancies. Recent reports suggest a role for EGFR signaling in proliferation and survival of neuroblastoma, a common form of pediatric cancer that often has an extremely poor outcome. METHODS: We examined ERBB family expression in neuroblastoma cell lines and patient samples by flow cytometry, western blot and Q-PCR. Response to ERBB inhibition was assessed in vitro by cell cycle analysis and western blot, and in vivo by serial tumor size measurements. RESULTS: A panel of neuroblastoma cell lines and primary patient tumors expressed EGFR, HER-3, and HER-4, with Her-2 in some tumors. Her-4 mRNA was expressed predominantly in cleavable isoforms. While EGFR inhibition with erlotinib and pan-ERBB inhibition with CI-1033 inhibited EGF-induced phosphorylation of EGFR, AKT, and ERK1/2, only CI-1033 induced growth inhibition and dose-dependent apoptosis in vitro. Both CI-1033 and erlotinib treatment of neuroblastoma xenograft tumors resulted in decreased tumor growth in vivo, though CI-1033 was more effective. In vivo expression of EGFR was observed predominantly in vascular endothelial cells. CONCLUSIONS: Pan-ERBB inhibition is required for ERBB-related neuroblastoma apoptosis in vitro, though EGFR contributes indirectly to tumor growth in vivo. Inhibition of EGFR in endothelial cells may be an important aspect of erlotinib's impact on neuroblastoma growth in vivo. Our results suggest that non-EGFR ERBB family members contribute directly to neuroblastoma growth and survival, and pan-ERBB inhibition represents a potential therapeutic target for treating neuroblastoma.